INNOVATIVE APPROACHES TO STRATEGIC MANAGEMENT OF TRADE ENTERPRISES (Development Service Industry Management, 2024)
The article studies innovative approaches to strategic management of trade enterprises. The article considers the concepts of innovation and innovation activity, specifies their role in management of a trade enterprise. The concept of innovation can be interpreted from different aspects, but scholars emphasise that innovation is the result of a certain process, the main purpose of which is to create a new or improved product that will bring commercial benefits to a potential innovator. Strategic management is a fairly young term, as it was introduced into scientific circulation at the turn of the 60s and 70s. The prerequisite for its emergence was the need to distinguish conceptual differences between current and long-term planning. The article studies the essence of strategic planning as a strategic instrument of trade business management, which is used by managers to achieve the set goals and objectives. The role of strategic management in the work of a trade enterprise is considered. The most well-known and relevant innovative approaches to strategic management, such as gamification, flexible workforce, e-tenders, shop-in-shop concept, etc. are described. We focus on the use of digital technologies in procurement activities, as this will help to automate the process of ordering from suppliers, accelerate the collection and processing of information, which gives more positive practical results. The experience of using these approaches in foreign trading companies is analysed, on the basis of which domestic trading enterprises should develop. The article also draws attention to the important role of personnel in the work of an enterprise, since it is the basis for building a successful business. It is concluded that for the further development of trade enterprises, it is necessary to continue researching innovative approaches to strategic management, taking into account foreign experience and testing it for domestic realities. Our businesses are already reaching the level of European companies and are gaining recognition and reputation. Therefore, despite the challenges of today, we should continue to develop the retail sector in Ukraine.
Keywords: trade enterprise; innovation; strategic management; trade; innovative approaches